A Voxel-Based Morphometry Study Reveals Local Brain Structural Alterations Associated with Ambient Fine Particles in Older Women - Casanova, Ramon; Wang, Xinhui; Reyes, Jeanette; Akita, Yasuyuki; Serre, Marc L.; Vizuete, William; Chui, Helena C.; Driscoll, Ira; Resnick, Susan M.; Espeland, Mark A.; Chen, Jiu-Chiuan (Frontiers in Human Neuroscience, 2016)
Objective: Exposure to ambient fine particulate matter (PM2.5: PM with aerodynamic diameters <2.5µm) has been linked with cognitive deficits in older adults. Using fine-grained voxel-wise analyses, we examined whether PM2.5 exposure also affects brain structure. Methods: Brain MRI data were obtained from 1,365 women (aged 71-89) in the Women’s Health Initiative Memory Study and local brain volumes were estimated using RAVENS (regional analysis of volumes in normalized space). Based on geocoded residential locations and air monitoring data from the U.S. Environmental Protection Agency, we employed a spatiotemporal model to estimate long-term (3-year average) exposure to ambient PM2.5 preceding MRI scans. Voxel-wise linear regression models were fit separately to gray matter (GM) and white matter (WM) maps to analyze associations between brain structure and PM2.5 exposure, with adjustment for potential confounders. Results: Increased PM2.5 exposure was associated with smaller volumes in both cortical GM and subcortical WM areas. For GM, associations were clustered in the bilateral superior, middle, and medial frontal gyri. For WM, the largest clusters were in the frontal lobe, with smaller clusters in the temporal, parietal, and occipital lobes. No statistically significant associations were observed between PM2.5 exposure and hippocampal volumes. Conclusions: Long-term PM2.5 exposures may accelerate loss of both GM and WM in older women. While our previous work linked WM decreased volumes to PM2.5 air pollution, this is the first neuroimaging study reporting associations between air pollution exposure and smaller volumes of cortical GM. Our data support the hypothesized synaptic neurotoxicity of airborne particles.